Investigation of Lipid Peroxidation and Antioxidant Capacity of Rats Fed with Various Oils - Kurbanli, Kamuran; Mehmetoglu, Idris (Asian Journal of Chemistry, 2010)
In this study, the effects of the oils such as butter, olive oil, sunflower oil and margarine on the serum lipid peroxidation, oxidized low density lipoprotein (LDL) and serum total antioxidant activity were investigated. Except control group, rats of all groups have been nourished by a special fodder embracing 15 % oil addition for a period of two months and were measured malondialdehyde (MDA), ox-LDL and antioxidant activity levels of samples. No significant difference was found in serum MDA and ox-LDL levels of the groups subjected to oil. However, when the serum total antioxidant activity levels were compared, it was noted that the measurements of olive oil group (1.08 ± 0.23 nmol/mL) were statistically higher (p < 0.05) than those of sunflower oil group (0,83 ± 0.12 nmol/mL). In addition to this, serum total antioxidant activity values of butter group (1.17 ± 0.14 nmol/mL) were statistically higher (p < 0.001) than those of sunflower group (0.83 ± 0.12 nmol/mL). It was found that MDA results decreased as: butter > margarine > olive oil > sunflower oil > control group and the antioxidant activity results decreased as: butter > control > olive oil > margarine > sunflower oil group. Butter gives the highest oxidized LDL and total antioxidant activity results and margarine gives the lowest oxidized low density, sunflower oil gives the lowest total antioxidant activity results.